Strides from the heart of Africa - Vanlauwe, Bernard (International Center for Tropical Agriculture, 2011)
The phase I of the Consortium for Improving Agriculturebased Livelihoods in Central Africa (CIALCA) project, initiated in 2006, succeeded in (i) characterizing the target areas, (ii) developing and evaluating technologies for improved productivity of banana- and legume-based systems, (iii) promoting improved nutrition and farmer-market linkages, (iv) building capacity, mainly of national system scientists (18 students trained at M.Sc. or Ph.D. level) and farmer groups (130 farmer groups trained), and (v) initiating partnerships to reach scale. CIALCA-I also broke new ground by establishing effective partnerships between institutes of the three target countries, which resulted in successful collaboration, sharing of resources, experiences, and ideas. While CIALCA-I focused most of its activities in specific action and satellite sites—comprising a limited number of households—within each mandate area, CIALCA-II aims at impact in the mandate areas. Phase II was initiated in 2009. The project’s overall goal is to improve the livelihoods of agriculture-based communities in Central Africa by enhancing their capacity to access and efficiently use the resources needed to improve system productivity, resulting in a better income, nutrition, and environment.